Autonomic Testing in Functional Gastrointestinal Disorders: Implications of Reproducible Gastrointestinal Complaints during Tilt Table Testing - Shaista Safder; Thomas C. Chelimsky; Mary Ann O'Riordan; Gisela Chelimsky (Gastroenterology Research and Practice)
Background: The pathophysiology of functional abdominal pain (FAP) is unknown. The upright portion of a tilt table test triggers typical symptoms in certain children. Aim: To compare the pathophysiology and treatment response of children with FAP whose gastrointestinal symptoms (GI) were replicated (RGI) by tilt table testing (TTT) to those in whom TTT did not have this effect (NRGI). Methods: An IRB-approved retrospective review of the autonomic laboratory database identified all children tested for GI complaints. We compared results of TTT, Valsalva maneuver, deep breathing and the axon reflex sweat test. Overall treatment response and that specific to fludrocortisone was ranked from 1 to 5, with 1 “much worse,” 3 “neutral,” and 5 “much better.” Results: 32/76 identified children had reproducible symptoms on TTT (RGI) and 44 did not (NRGI). The RGI group was younger, had a shorter duration of symptoms, more postural tachycardia syndrome (POTS) and benefited more from fludrocortisone (73% in RGI vs. 25% in NRGI). Conclusion: Dividing patients with FAP according to the effect of TTT on their symptoms appears to delineate 2 fundamentally different groups, with potentially different pathophysiologies and treatment responses. A prospective study is needed.